Acute Stress-Induced Coagulation Activation in Patients With Remitted Major Depression Versus Healthy Controls and the Role of Stress-Specific Coping. Issue 8 (11th February 2020) - von Känel, Roland; Merz, Franziska; Pfister, Hildegard; Brückl, Tanja; Zimmermann, Petra; Uhr, Manfred; Holsboer, Florian; Höhne, Nina; Ising, Marcus
Abstract: Background: Depressed patients have an increased risk of myocardial infarction, for which acute stress is a frequent trigger. Prothrombotic changes could be one involved mechanism that can be modulated by psychological coping. Purpose: We examined the effects of remitted major depression and situation-specific coping strategies on stress-induced coagulation activation. Methods: Forty patients with remitted depression and 23 healthy controls underwent the Trier Social Stress Test, rating applied coping strategies thereafter. Blood was sampled at baseline and 15 and 45 min poststress to measure fibrinogen, von Willebrand factor (VWF) and D-dimer. Coagulation activation over time was quantified as area under the curve (AUC) with respect to baseline activity. Standardized z-scores of individual coagulation AUC measures were added up to a prothrombotic index. Results: Stress provoked significant VWF ( p = .024) and D-dimer ( p = .002) responses. Remitted depressed patients used positive distraction coping more frequently than controls did ( p = .030). Coagulation AUC measures were similar in both groups. In all participants, higher positive coping total ( p = 0.009), driven by devaluation/defense ( p = .022) and distraction ( p = .004) coping, was associated with a lower prothrombotic index. In controls, but not in remitted depressed patients, higher positive coping total ( p = .008), driven by higher devaluation/defense ( p = .010) and distraction ( p = .023) coping, was associated with lower VWF AUC. Conclusions: Despite the use of favorable coping strategies in a specific stress situation, remitted depressed patients may benefit less from a positive effect of positive situational coping on coagulation activation than controls. Such a mechanism could partially explain the increased risk of myocardial infarction in depressed individuals. Abstract : Adaptive coping strategies with an acute stress task were associated with lower stress-induced acceleration of blood clotting, but this heart-protective effect seemed to be weaker in patients with remitted depression than in healthy persons